2009
DOI: 10.1111/j.1574-6968.2009.01736.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of expression and biochemical characterization of a β-class carbonic anhydrase from the plant growth-promoting rhizobacterium,Azospirillum brasilenseSp7

Abstract: Carbonic anhydrase (CA; [EC 4.2.1.1]) is a ubiquitous enzyme catalysing the reversible hydration of CO(2) to bicarbonate, a reaction that supports various biochemical and physiological functions. Genome analysis of Azospirillum brasilense, a nonphotosynthetic, nitrogen-fixing, rhizobacterium, revealed an ORF with homology to beta-class carbonic anhydrases (CAs). Biochemical characteristics of the beta-class CA of A. brasilense, analysed after cloning the gene (designated as bca), overexpressing in Escherichia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
(52 reference statements)
0
14
0
Order By: Relevance
“…5). The expression of several heterotrophic b-CAs has been reported to be induced by low CO 2 (Aguilera et al, 2005;Amoroso et al, 2005;Kaur et al, 2009), whereas the expression of others is regulated by additional or alternative factors including growth rate, pH or stress (Kaur et al, 2009;Merlin et al, 2003). The differential expression of psCA proteins suggests their independent regulation and further supports the hypothesis that they play different physiological roles in P. aeruginosa.…”
Section: Psca1 Psca2 and Psca3 Are Functionally Active Casmentioning
confidence: 62%
“…5). The expression of several heterotrophic b-CAs has been reported to be induced by low CO 2 (Aguilera et al, 2005;Amoroso et al, 2005;Kaur et al, 2009), whereas the expression of others is regulated by additional or alternative factors including growth rate, pH or stress (Kaur et al, 2009;Merlin et al, 2003). The differential expression of psCA proteins suggests their independent regulation and further supports the hypothesis that they play different physiological roles in P. aeruginosa.…”
Section: Psca1 Psca2 and Psca3 Are Functionally Active Casmentioning
confidence: 62%
“…Such convergent evolution among diverse groups of organisms suggests that CAs are fundamental to many life strategies (Smith et al, 1999). Indeed, these enzymes have been linked to a number of common and specialised biological processes, such as CO 2 concentration mechanisms required to maintain photosynthesis in plants, algae and cyanobacteria (Badger, 2003;Badger and Price, 1994); calcification to limit calcium toxicity in bacteria (Banks et al, 2010;Li et al, 2005b); maintenance of required CO 2 and bicarbonate levels for metabolic activity in both bacteria (Merlin et al, 2003) and fungi (Kaur et al, 2009) growing under CO 2 limited conditions; and metabolic flexibility in methanogenic archaea (Smith and Ferry, 2000). However, despite evidence of CA activity in soils, the variability and drivers of their expression by soil communities is poorly understood (Li et al, 2005a;Seibt et al, 2006;Wingate et al, 2009Wingate et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Cell extracts of A. brasilense showed very low level of carbonic anhydrase activity of 0.3 ± 0.1 U/mg. Since A. brasilense genome also encodes a functional β-CA [13], it was not clear if the observed CA activity was due to β-CA or also due to γ-CA. To determine whether gca1 is expressed in A. brasilense under ambient conditions, RT-PCR with RNA samples isolated from the mid-log phase cultures grown in minimal (MMAB) or rich (LB) medium was performed.…”
Section: Resultsmentioning
confidence: 99%
“…A. brasilense genome revealed the presence of one β-CA and two putative γ-CA encoding genes. Recently, we have shown that β-CA gene in A. brasilense encoded a functionally active protein, and its expression was regulated by growth phase, CO 2 concentration and pH [13]. In this work, one of the putative ORFs whose amino acid sequence shared significant identity with other members of the γ-CA family was characterized.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation